Traditional Village research based on culture-landscape genes: a Case of Tujia traditional villages in Shizhu, Chongqing, China - Guoqing Li; Binqing Chen; Jie Zhu; Lei Sun (Journal of Asian Architecture and Building Engineering, 2024)
Global urbanization has led to severe damage and even disappearance of traditional villages in large numbers, significantly impacting the diversity of cultural landscapes. To effectively protect and inherit the cultural landscape of traditional villages, this study proposes the “culture-landscape genes” theory and its double-chain model. Taking the traditional Tujia villages in Shizhu County, Chongqing Municipality, China as an example, we identify, extract, correspond, encode, and comprehensively evaluate their culture-landscape genes. Based on the evaluation and analysis results, corresponding protection and development strategies are formulated. The study indicates that: firstly, the identification, extraction, and correlation of genes directly influence the construction of the evaluation system and the assessment of the protection level. Secondly, the comprehensive evaluation system under the double-chain model is more scientific and reasonable compared to the single-gene model of cultural or landscape genes. The culture-landscape genes theory proposed in this study promotes the development of the gene theory of traditional villages, and its double-chain research model effectively supplements the current methods for the protection and sustainable development of traditional villages, demonstrating a wide range of application value.